1999
DOI: 10.1111/0023-8333.00094
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological Beliefs and Language Learning Beliefs: What Do Language Learners Believe About Their Learning?

Abstract: This study (a) examines the structure of language learners' beliefs about learning in general and beliefs specifically about language learning and (b) explores the relationship between the 2 belief domains. A belief questionnaire was administered to 187 college students learning Japanese as a foreign language. Factor analyses identified 5 dimensions of general epistemological beliefs comparable to those reported by Schommer (1990Schommer ( , 1994b, and 6 dimensions of language learning beliefs. Although there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
1
14

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(203 citation statements)
references
References 60 publications
10
169
1
14
Order By: Relevance
“…Using the Beliefs About Language Learning Inventory (BALLI), which consists of 34 statements 1 that assess student beliefs in five areas-(a) the difficulty of language learning, (b) foreign language aptitude, (c) the nature of language learning, (d) language learning and communication strategies, and (e) motivation and expectations- Horwitz (1987Horwitz ( , 1988 confirmed that learners of various linguistic and cultural backgrounds share certain beliefs about learning. Other studies showed that learners' epistemological beliefs (i.e., beliefs about the nature of learning) differ from those about language learning (Mori, 1999), suggesting that learners perceive learning in general differently from learning about specific subjects and concepts. Loewen et al (2009), for example, showed that learners view grammar instruction and CF as distinct categories, and the authors have called for future research to consider this differentiation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Beliefs About Language Learning Inventory (BALLI), which consists of 34 statements 1 that assess student beliefs in five areas-(a) the difficulty of language learning, (b) foreign language aptitude, (c) the nature of language learning, (d) language learning and communication strategies, and (e) motivation and expectations- Horwitz (1987Horwitz ( , 1988 confirmed that learners of various linguistic and cultural backgrounds share certain beliefs about learning. Other studies showed that learners' epistemological beliefs (i.e., beliefs about the nature of learning) differ from those about language learning (Mori, 1999), suggesting that learners perceive learning in general differently from learning about specific subjects and concepts. Loewen et al (2009), for example, showed that learners view grammar instruction and CF as distinct categories, and the authors have called for future research to consider this differentiation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…
This study compared the beliefs college-level students hold about corrective feedback in different learning contexts: English as a second language (Canada, n = 197) and English as a foreign language (Russia, n = 224 Learner beliefs, defined as learners' metacognitive knowledge about learning (Wenden, 1999), are seen as "significant learner characteristics to take into account when explaining learning outcomes" (Dörnyei & Ryan, 2015, p. 187) because they shape and affect the way learners go about the task of learning (e.g., Breen, 2001; Fox, 1993;Horwitz, 1985Horwitz, , 1999Mori, 1999;Tanaka, 2004 learners hold about language acquisition, but also revealed factors that could shape those beliefs. These may include
…”
mentioning
confidence: 99%
“…These theories and methods constructed my beliefs which in turn affected my practices and strategies in both learning and teaching. Some of these beliefs relate to the nature of knowledge and affect the status of professionalism (Mori, 1999). Indeed, these beliefs can be considered crucial in the development of knowledge (Hofer & Pintrich, 1997 Fendler, 2003, p. 18).…”
Section: A Teachers' Role In the Professional Development Programmesmentioning
confidence: 99%
“…For example, considering the beliefs and opinions of language learners, strategic participants of learning and teaching, and taking their opinions into account accordingly before making any decisions about teaching appears reasonable, especially if the approach to curriculum design is school-based, as learners' beliefs about language learning might influence their performance. This has been acknowledged by (Mori, 1999;Ariogul, Unal, and Onursal, , 2009;Trinder, 2013). The means by which the beliefs and opinions of language learners was gathered was through a questionnaire.…”
Section: The Studymentioning
confidence: 99%